Fault diagnosis and fault tolerant control using set-membership approaches: application to real case studies - Puig, Vicenç (Zielona Góra: Uniwersytet Zielonogórski)
This paper reviews the use of "set-membership methods" in "fault diagnosis" (FD) and "fault tolerant control" (FTC). Setmembership methods use a deterministic unknown-but-bounded description of noise and parametric uncertainty ("intervalmodels"). These methods aims at checking the consistency between observed and predicted behaviour by using simple sets to approximate the exact set of possible behaviour (in the parameter or the state space)
Keywords: fault detection and isolation; fault-tolerant control; robustness; interval models; set-membership